AB1047 Autoimmune Diseases in Patients with Acute Coronary Syndrome Subject to Coronary Angiography. (10th June 2014) - Miretti, E.M.; Lema, L.; Haye Salinas, M.; Quino, V.; Barroso, M.V.; Serra, C.; Caeiro, F.; Alvarellos, A.; Saurit, V.
Abstract : Background: There is growing evidence that atherosclerosis (ATE) is not explained only by traditional cardiovascular (CV) risk factors and that chronic inflammation should be considered as an additional cause 1, 2, 3 . Autoimmune diseases (AD) are characterized by chronic systemic inflammation and many studies have reported that ATE occurs more frequently, at an accelerated pace and younger age in patients with AD. 6, 7, 8 Most studies looked at the frequency of ATE developing in series of patients with autoimmune diseases; only a few studies addressed the prevalence of AD in series of patients with acute coronary syndrome (ACS) undergoing coronary angiography (CA). Objectives: 1. To assess the frequency of AD in patients studied for ACS. 2. To compare patients with and without AD for differences in demographic characteristics, coronary disease risk factors, severity and extension of vessel involvement. Methods: We included every patient >18 years old who underwent CA for ACS from 01 Jan 2007 to 01 Jan 2012 in two reference centers in Cόrdoba, Argentina, studied in a retrospective observational and analytical way. Study approved by the ethics committee of both centers. ACS was defined as: Unstable angina (UA), non-Q wave myocardial infarction (MI) and Q wave MI. Coronary artery disease was defined as significant arterial stenosis: when ≥70% of anterior descending artery, circumflex or right coronary artery or ≥50% left main coronary artery (LMCA). Multivessel coronary disease (MVCD): ≥70% stenosis in ≥2 vessels. We calculated m (SD) for continuous variables. We compared patients with and without AD by t-test. Frequencies were calculated for categorical variables and the two groups were compared by x2 or Fisher test when appropriate. Statistical analysis with SPSS. Significant P≤0.05. Results: Total N: 954 patients; 23 (2.4%) had AD: 10 patients had Rheumatoid Arthritis (RA) (43.5%) with a mean duration of the disease of 10.10 years, 3 Systemic Lupus Erythematosus (SLE) (13%) with a mean duration of 14, 67 years, Other 10 AD were: Sjögren's syndrome (2 patients), Polymyositis (2 patients), Polymyalgia Rheumatica (2 patients), Psoriatic Arthritis (1 patient), Henoch Schönlein Purpura (1), Temporal Arteritis (1) and Autoimmune Hepatitis (1). Demographic, CA and treatment characteristics are shown in Table 1 : there was a significant female predominance (p 0.009) and a lower prevalence of dislypidemia (p 0.035) in AD patients. Although it did not reach statistical significance, there was a tendency to a younger age in patients with AD. Conclusions: There was a low frequency of patients with AD in the population with ACS undergoing CA, and they were mostly women and had less dyslipidemia than those without AD. RA and SLE were the most prevalent AD both with a long standing course. There was no difference in terms of vessel affection or revascularization therapy. References: Inmaculada del Rincόn, Arthritis Rheum. 2001 Dec;44(12):2737-45. KMJ Douglas, Ann Rheum Dis 2006;65:348-353. A Gonzalez, Ann Rheum Dis 2008 67:64-69. Hasya Zinger, Clinic Rev Allerg Immunol 2009, 37: 20-28. Yehuda Shoenfeld, Circulation 2005; 112:3337-3347. Jane Salmon, Am J Med 2008 October; 121 (10 Suppl 1): S3-S8. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1437